Ecosystem approach to coral fish management domain fishing techniques at PPI Ie Meulee, Sabang City - Ayu Sriwulanda; Alvi Rahmah; Imelda Agustina; Ratna Mutia Aprilla; Abel Muammar Mesha (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The study was conducted froam June to July 2024 located in PPI Ie Meulee, Sukajaya District, Sabang city, Aceh Province. The data collection methods include primary data (interviews and questionnaire) and secondary data (from relavant institutions and references). The sampling was done using the purposive sampling method with 21 respondents. Data analysis used was ordinal-based on liker 1,2,3 to each indicator, such as destructive or illegal fishing methods, modifications to fishing gear and auxiliary equipment, fishing capacity and effort, catch selectivity, the compliance of the function and size of fishing vessels with legal documents, and the certification of fishing crew members according to regulations. The overall average indicator score are 3. The results of the study showed that the fishing technique domain was categorized as good, with a composite value of 75.00.Keywords:EAFMFishing TechnuquesKota Sabang